Efektivitas Ekstrak Daun Kemangi (Ocimum sanctum Linn) Terhadap Mortalitas Larva Aedes aegypti - Oktafian Diyas Tamtama; Dita Pratiwi Kusuma Wardani; Muhammad Luthfi Almanfaluthi; Isna Hikmawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Basil leaf (Ocimum sanctum Linn) are known to have the ability as natural larvicides because there are various compounds including tannins, eugenol, flavonoids, essential oils, hexauronic acid, saponins, pentose, xylose, metal homocytic acid, mulludistin, ursolic acid and methyl clavical. This study aims to determine the effectiveness of basil leaf extract (O. sanctum Linn) on mortality of Aedes agypti larvae. This research is a true experimental type with posttest only with control group design. Aedes aegypti larvae obtained from Balitbangkes Banjarnegara were used in this study as many as 450 larvae. This study consisted of 6 groups with 2 control groups (positive control/temefos 1% and negative control/distilled water) and 4 other groups receiving treatment with basil leaf extract concentrations of 1.5%, 1.8%, 2.1%, and 2.4%. Each group contained 25 larvae of Ae. aegypti with three repetitions and observation time with 10th, 40th, 60th, 120th, 240, 720, and 1440 minute intervals. Larval mortality of Ae. aegypti occurred from the 120th minute with a concentration of 2.4% with a mortality percentage of 5.6%. The results of the Kruskal Wallis test showed that there were differences in the mortality of Ae. aegypti at 60, 120, 240, 720, and 1440 minutes. The LC50 value was 2.329% at 720 minutes while the LC90 test was 7.043% at 720 minutes. Basil leaf extract has not been effective as a larvicide because mortality occurred from the 120th minute.